Distinct and complementary roles for Aspergillus fumigatus‐specific Tr1 and Foxp3+ regulatory T cells in humans and mice. Issue 8 (13th May 2014) - Bedke, Tanja; Iannitti, Rossana G; De Luca, Antonella; Giovannini, Gloria; Fallarino, Francesca; Berges, Carsten; Latgé, Jean‐Paul; Einsele, Hermann; Romani, Luigina; Topp, Max S
Abstract : Unlike induced Foxp3 + regulatory T cells (Foxp3 + iTreg ) that have been shown to play an essential role in the development of protective immunity to the ubiquitous mold Aspergillus fumigatus, type‐(1)‐regulatory T cells (Tr1) cells have, thus far, not been implicated in this process. Here, we evaluated the role of Tr1 cells specific for an epitope derived from the cell wall glucanase Crf‐1 of A. fumigatus (Crf‐1/p41) in antifungal immunity. We identified Crf‐1/p41‐specific latent‐associated peptide + Tr1 cells in healthy humans and mice after vaccination with Crf‐1/p41+zymosan. These cells produced high amounts of interleukin (IL)‐10 and suppressed the expansion of antigen‐specific T cells in vitro and in vivo . In mice, in vivo differentiation of Tr1 cells was dependent on the presence of the aryl hydrocarbon receptor, c‐Maf and IL‐27. Moreover, in comparison to Tr1 cells, Foxp3 + iTreg that recognize the same epitope were induced in an interferon gamma‐type inflammatory environment and more potently suppressed innate immune cell activities. Overall, our data show that Tr1 cells are involved in the maintenance of antifungal immune homeostasis, and most likely play a distinct, yet complementary, role compared with Foxp3 + iTreg .